Effect Of Vegetable Oil On Surface Roughness During Turning Of Aisi 1020 Steel - Hing, Chen Teng (Universiti Sains Malaysia, 2021)
Surface quality is vital to determine the functionality and quality of the machined product. Most studies have implemented arithmetic average height (Ra) to evaluate the surface finish of machined product, however deviation from theoretical knowledge was observed as this parameter provides only the vertical amplitude of roughness deviation which was inadequate. In this research, turning operations of workpiece made of AISI 1020 low carbon steel were carried out at varying spindle speeds including 1000, 1500 and 2000 rpm, at constant feed rate 0.20 mm/rev and depth of cut 0.5mm. The machining condition was divided into dry and wet turning using palm oil as cutting fluids. In dry turning, Ra, Rt and Rq values dropped when the spindle speed increased from 1000 to 1500 rpm, but then reversed when the spindle speed was further increased to 2000 rpm. For wet turning, the amplitude roughness values were doubled lower at spindle speed 1000 and 2000 rpm, but slightly higher at 1500 rpm compared to dry turning. Cross-correlation analysis also had been completed for roughness assessment and the result obtained are almost similar. Whereas using Rsk and Rku parameters, wet turning outperformed dry turning at both lower spindle speeds, but the result was opposite at the highest spindle speed implemented. The findings can be summarized as turning under palm oil lubricating condition able to improve surface quality in align with suitable process parameters, while more roughness parameters had to be deployed to ensure the reliability of improvements.